2023
DOI: 10.3390/nu15040898
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of CalFresh Participation and Food Insecurity on Academic Outcomes among College Students during the COVID-19 Pandemic

Abstract: Food insecurity (FI) is associated with many adverse outcomes in college students. The Supplemental Nutrition Assistance Program (SNAP, known as CalFresh in California) has been observed to alleviate FI; however, on college campuses, the benefits of food assistance programs are not well understood. This study investigated whether college students benefit from CalFresh participation. It was hypothesized that students would experience increased FI over time and that CalFresh participation would moderate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…At the federal level, the Enhance Access to SNAP (EATS) Act (2023) seeks to address this issue by expanding SNAP student eligibility, which would benefit graduate students who do not meet work requirements due to their funding source. Nevertheless, receiving SNAP assistance has shown to lessen the impact of food insecurity on undergraduate and graduate students' grade point average during the pandemic, highlighting the importance of expanding SNAP access (Loofbourrow et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…At the federal level, the Enhance Access to SNAP (EATS) Act (2023) seeks to address this issue by expanding SNAP student eligibility, which would benefit graduate students who do not meet work requirements due to their funding source. Nevertheless, receiving SNAP assistance has shown to lessen the impact of food insecurity on undergraduate and graduate students' grade point average during the pandemic, highlighting the importance of expanding SNAP access (Loofbourrow et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Bergdahl et al found that for students experiencing food insecurity, government supports in the form of stimulus payments to students from low-income backgrounds were most helpful for alleviating food insecurity [154]. Federal stimulus payments were also observed to be of particular benefit to students when combined with SNAP benefits at a large California university [155]. Unfortunately, resource availability was not stable for all college students nationwide; such differences in resource availability for vulnerable students may exacerbate inequities and compound negative experiences during times of acute stress or emergency [156].…”
Section: Food Security Concerns In Response To External Shocks: Covid-19mentioning
confidence: 99%
“…Numerous college food insecurity studies have been conducted in the U.S. [132][133][134][135][136][137]. More specifically, several state and regional assessments have been conducted in Maryland and the Mid-Atlantic area [138,139] Illinois [140], Oregon [141], California and the western U.S. [142][143][144][145][146], and Georgia and the southeastern U.S. [147][148][149]. Research conducted at Michigan State University shows that in 2020, 39% of the students reported low or very low food security [46].…”
Section: Measuring Food Access In Lansing and East Lansingmentioning
confidence: 99%